Electrodeposited Heusler alloy films with enhanced magneto-optical property. (December 2020) - Karim, M.R.; Panda, D.; Adhikari, A.; Sharangi, P.; Mandal, P.; Ghosh, S.; Bedanta, S.; Barman, A.; Sarkar, I.
Graphical abstract: Highlights: Modified electrodeposition method for sub-micron thin Heulser alloy film growth. Large magneto optic Kerr rotation up to 300 mdeg exhibited with reduced thickness. Thin film growth of thermodynamically difficult to form Heusler system. Abstract: Growth of Heusler alloy films through techniques other than conventional physical vapor deposition presents a challenge for spintronic materials research. In this study an electrochemical deposition approach for these alloys is demonstrated in which sub-micron thickness control can be achieved. By using magneto optic Kerr effect and Kerr microscopy measurements a systematic study of surface magnetization reversal behavior of these films is presented. The results demonstrate that the growth of sub-micron films of Co2 FeSn leads to significant enhancement in magneto optic Kerr rotation. A large Kerr rotation value up to 300 mdeg was observed for thin films of thickness ∼200 nm. The modified scheme reported here opens up a path for exploration of electrochemical method as a facile route for fabricating Heusler alloys with improved surface property.